FOREIGN DIRECT INVESTMENT AND ECONOMIC GROWTH IN TIMES OF ECONOMIC CRISIS: EVIDENCE FROM SOUTHEAST EUROPEAN COUNTRIES - Kragulj, Dragana; Parezanin, Milos (European Scientific Journal, ESJ, 2015)
Countries of Southeast Europe are at different levels of economic growth and accession to the European Union. Bulgaria, Romania and Croatia are already valid members of the EU. While Albania, Macedonia, Montenegro and Serbia have the status of the candidates for membership, Bosnia and Herzegovina still waits for the status of candidate for the accession to the EU. The common thing for all the referred countries is that they are far away from other members of the EU regarding their economic development. Therefore, foreign direct investments appear to be an important factor of speeding up the economic growth of these countries. Linear correlation between the foreign direct investments and the indicators of economic growth in the countries of the Southeast Europe is analyzed in the paper. The period before the economic crises and the period after the beginning of the economic crisis are analyzed separately, in order to observe the linear correlation between FDI and economic growth. The following variables are taken as indicators of the economic growth: GDP per capita, export, import and rate of unemployment. The results of the research speak in favor of the existence of a statistically significant correlation between FDI and other macroeconomic indicators in the period before the economic crisis in the majority of the analyzed countries. After the beginning of the economic crisis, the linear correlation has been extremely weak. Effects of the crisis very strongly influenced the economies of the observed countries.